Multibeam bathymetry raw data (Kongsberg EM710 entire dataset) of RV SONNE during cruise SO276 - Saskia Brix-Elsig; James Taylor; Morgane Le Saout; Mia Schumacher; Thorsten Lux (PANGAEA, 2023)
Raw multibeam bathymetry data were recorded on RV SONNE during SO276 using Kongsberg EM710 multibeam echosounder. The cruise took place between 2020-06-22 - 2020-07-26 in the Atlantic Ocean. Data were recorded throughout the whole time spend outside EEZs in areas shallower than 1500m with an approximate average depth of around 400m. To enhance MBES data accuracy, CTD casts were made in the working area prior to each MBES survey using CTD rosette to raytrace beams with the obtained sound velocity profiles (SVP). During transits, SVPs from the WOA13 were applied via Sound Speed Manager Software to the data directly during acquisition with SIS Seafloor Information System. Data are unprocessed and can therefore contain incorrect depth measurements (artifacts) without further processing. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus SVP files are added to this dataset. Data acquisition and provision were accomplished within work package 2 of the EU Horizon 2020 project iAtlantic- Integrated Assessment of Atlantic Marine Ecosystem in Space and Time (https://www.iatlantic.eu/) IceAge project.